Climate change and agriculture in Zimbabwe: sustainability in minority farming communities - Matsa, Mark (Springer Cham, 2022)
Introduction This book proves, through empirical research, that indigenous and traditional agricultural communities have experienced severe climate change impacts, and have developed corresponding livelihood strategies to strengthen their resilience in a variable climate. With a focus on indigenous minority farming communities in the developing region of South-Western Zimbabwe, the study presents both qualitative and quantitative approaches of data analysis to assess sustainability problems amid climate change and climate variability challenges, and proposes potential solutions. In eight chapters, the book expands on the scarce availability of community-based research on climate change and variability in Zimbabwe.